2005
DOI: 10.1093/sleep/28.11.1405
|View full text |Cite
|
Sign up to set email alerts
|

Association of Psychiatric Disorders and Sleep Apnea in a Large Cohort

Abstract: Sleep apnea is associated with a higher prevalence of psychiatric comorbid conditions in Veterans Health Administration beneficiaries. This association suggests that patients with psychiatric disorders and coincident symptoms suggesting sleep-disordered breathing should be evaluated for sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
264
2
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(290 citation statements)
references
References 42 publications
16
264
2
8
Order By: Relevance
“…To the best of this author's knowledge there is not currently evidence available from large community samples that indicate whether the relationship between sleep apnea and anxiety disorders is greater than would be expected by random association. An analysis from the large Veteran's Administration Healthcare data base, however, did indicate an increased association of diagnoses of "anxiety" and PTSD (as well as other psychiatric disorders) with sleep apnea (60).…”
Section: Sleep Anxiety Symptoms and Sleep Apneamentioning
confidence: 87%
“…To the best of this author's knowledge there is not currently evidence available from large community samples that indicate whether the relationship between sleep apnea and anxiety disorders is greater than would be expected by random association. An analysis from the large Veteran's Administration Healthcare data base, however, did indicate an increased association of diagnoses of "anxiety" and PTSD (as well as other psychiatric disorders) with sleep apnea (60).…”
Section: Sleep Anxiety Symptoms and Sleep Apneamentioning
confidence: 87%
“…One important line of research builds upon findings from several large-scale epidemiological studies, which have demonstrated that approximately 20% of depressed patients exhibit a frequently undiagnosed sleep-disordered breathing, mostly obstructive sleep apnea [28,29]. This goes in line with a large number of reports which have gathered data linking metabolic syndrome and, most importantly, obesity and diabetes or insulin resistance, together with elevated inflammatory markers, to both sleep-disordered breathing and depression [30][31][32][33][34][35][36].…”
Section: Eds and Depressionmentioning
confidence: 89%
“…6 In patients with a sleep disorder, the prevalence of depression has been reported to be 17.6% 7 ; in patients with OSA in particular, its prevalence is even higher, ranging from approximately 20% to 40% when assessed using the Beck Depression Inventory. 5,8,9 Progression of OSA has been found to be associated with an increased risk of developing depression. 10 Even patients with mild OSA are 60% more likely to become depressed than individuals without this sleep disorder.…”
Section: Depression In Patients With Osamentioning
confidence: 99%
“…In a study of a large cohort of nearly 120,000 veterans treated in US hospitals, anxiety, posttraumatic stress disorder, and psychosis were found in significantly more patients with OSA than in patients who did not have this sleep disorder (16.7%, 11.9%, and 5.1%, respectively; P < .0001). 5 The aims of this review are to examine the relationship between OSA and depression and also to describe how OSA and ES can be recognized in the primary care setting. The role of the primary care physician (PCP) in supporting, monitoring, and educating patients during treatment for OSA will also be discussed.…”
mentioning
confidence: 99%